The Relevance of Fair Value Across Countries: Firms Listed in Lisbon and Madrid Stock Exchange - José Carlos Rocha da Veiga (Journal of Spatial and Organizational Dynamics, 2015)
Following the theories of gray and positive accounting this study examines the options in the measurement of assets and the usefulness of fair value. Using a sample of 104 Portuguese and Spanish companies with listed securities, the research analyzes factors associated with the fair value option and whether the listing incorporates this information. The results reveal a conservative behavior, where only 19% of companies use the fair value, specially the Portuguese (35%), confirming that the country of origin has a significant influence on this choice. The fair value option is more expressive on investment properties, and less expressive in intangibles. The sectors denote significantly different behaviors, and companies with higher quotes are more cautious using the fair value. The market reacts differently about the nature of this information. It is favorable to its sectorial utilization, reacting negatively to a more widespread use (Portugal), which supports the argument that the relevance of fair value estimates are dependent on the confidence placed by investors. This study contributes to stress the culture and market price of companies as explanatory variables for the use of fair value. Our findings suggest a more conservative culture in Spanish than in Portuguese companies.